Palynology of the northwestern Mediterranean shelf (Gulf of Lions): First vegetational record for the last climatic cycle (Marine and Petroleum Geology, 2005)
Palynology has been performed for the ﬁrst time on Late Quaternary sediments of the Gulf of Lions. The aim is both to tighten the chronology of seismic proﬁles in the region, and to elucidate the vegetation of southern France during the Last Climatic Cycle. Four cores, taken on the shelf, mostly record Marine Isotope Stages (MIS) 1 and 2 and part of MIS 3 and MIS 5. The latter sediments might have been preserved in a paleodepression on the emergent shelf between the Rhoˆne and the He´rault rivers. It would explain their preservation against transgression and regression erosions of more recent stages. This study also provides a synthesis of palynological continental data collected during the last 40 years in southern Europe. Preliminary comparisons made between the latter and new marine data demonstrate that refugia of Picea and Abies existed in southern France during MIS 3 and MIS 2. The dynamics of Artemisia, deciduous Quercus and Corylus, Abies and ﬁnally Fagus is also reconstructed for the last deglaciation. First results obtained in the Gulf of Lions conﬁrm and complete that synthesis.

Palynology of the northwestern Mediterranean shelf (Gulf of Lions): First vegetational record for the last climatic cycle - Beaudouin, Célia; Suc, Jean-Pierre; Acherki, Nabila; Courtois, Laurent; Rabineau, Marina; Aloïsi, Jean-Claude; Sierro, Fransisco Javier; Oberlin, Christine (Marine and Petroleum Geology, 2005)
Palynology has been performed for the ﬁrst time on Late Quaternary sediments of the Gulf of Lions. The aim is both to tighten the chronology of seismic proﬁles in the region, and to elucidate the vegetation of southern France during the Last Climatic Cycle. Four cores, taken on the shelf, mostly record Marine Isotope Stages (MIS) 1 and 2 and part of MIS 3 and MIS 5. The latter sediments might have been preserved in a paleodepression on the emergent shelf between the Rhoˆne and the He´rault rivers. It would explain their preservation against transgression and regression erosions of more recent stages. This study also provides a synthesis of palynological continental data collected during the last 40 years in southern Europe. Preliminary comparisons made between the latter and new marine data demonstrate that refugia of Picea and Abies existed in southern France during MIS 3 and MIS 2. The dynamics of Artemisia, deciduous Quercus and Corylus, Abies and ﬁnally Fagus is also reconstructed for the last deglaciation. First results obtained in the Gulf of Lions conﬁrm and complete that synthesis.
Keywords: late quaternary; nw mediterranean sea; palynology